2021
DOI: 10.1177/26349833211000058
|View full text |Cite
|
Sign up to set email alerts
|

3D printing of a continuous fiber-reinforced composite based on a coaxial Kevlar/PLA filament

Abstract: Additive manufacturing has allowed for the production of complex and mass customized geometries, but often at the expense of mechanical performance, a penalty which can be in part mitigated with the fabrication of composite parts. Thermoplastic structures fabricated with material extrusion additive manufacturing stand to be improved in terms of fracture toughness with the integration of continuous fibers. The present research program has investigated the production of a continuously reinforced filament to be u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Furthermore, unlike conventional drilling techniques involving structural damage, in 3D printing samples, such damage is not anticipated [ 38 , 39 , 40 , 41 ]. Moreover, 3D printing technology needs to be improved, particularly in the context of enhancing interfacial compatibility between different types of fibers and polymer matrices and maintaining a precise orientation level [ 42 ]. Plasma treatment of fibers [ 43 ], interfacial grafting [ 44 ], and tailoring fiber orientations [ 45 ] are the critical approaches that can be employed to enhance the interfacial interactions between polymer and fiber during 3D printing.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, unlike conventional drilling techniques involving structural damage, in 3D printing samples, such damage is not anticipated [ 38 , 39 , 40 , 41 ]. Moreover, 3D printing technology needs to be improved, particularly in the context of enhancing interfacial compatibility between different types of fibers and polymer matrices and maintaining a precise orientation level [ 42 ]. Plasma treatment of fibers [ 43 ], interfacial grafting [ 44 ], and tailoring fiber orientations [ 45 ] are the critical approaches that can be employed to enhance the interfacial interactions between polymer and fiber during 3D printing.…”
Section: Resultsmentioning
confidence: 99%
“…PLA filaments reinforced with kevlar fibers were tested for their impact resistance and found that the impact resistance improved with the increased addition of fibers. To produce these continuously reinforced 3D printed components, no modifications are need to be done in the existing printers [27]. A sandwich panel with flexible core and stiff upper and lower surfaces made of filaments reinforced with glass fibers are tested for its energy absorbance.…”
Section: Introductionmentioning
confidence: 99%
“…Composite materials reinforcement using continuous glass fibers through AM has been also investigated with significant mechanical property improvements [31][32][33]. Furthermore, it has been reported that incorporating continuous Kevlar fibers not only enhances the tensile properties of PLA and nylon matrixes, but also effectively improves their impact resistance [34,35].…”
Section: Introductionmentioning
confidence: 99%